(untitled) (COLOMBIAN JOURNAL OF ADVANCED TECHNOLOGIES, 2021)
Pet food dispensers have been one of the equipment that has become the most popular in recent years, since they allow feedinganimals from a distance, without altering the pace of life of the owners, this constitutes an advantage, due to the intricate airline requirements for traveling with pets; and access restrictions at some establishments. However, the supply of automatic dispensers in the Colombian market is limited in terms of costs, the prices of the dispensers range between approximately 300,000 and 700,000, thus creating a barrier to access to said devices, given the socioeconomic conditions of the country. Therefore, it is proposed to design an automatic pet food dispenser for small breeds that maintains the quality and services of current dispensers but is affordable to most Colombian families. The prototype is still in the design phase, only 2 stages have been partially developed, a documentary review of the characteristics of the dispensers offered on the market has been carried out and a preliminary design has been proposed.